2019
DOI: 10.1136/bcr-2018-228428
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive global cerebral atrophy in the setting of anti-LGI1 encephalitis

Abstract: A 47-year-old man presented with complaints of breakthrough seizures, psychiatric and behavioural changes and catatonic features. MRI of the brain showed mild cerebral and right hippocampal atrophy, while the electroencephalogram showed intermittent right temporal slowing. With a presumed diagnosis of autoimmune encephalitis, he was treated with intravenous immunoglobulin (IVIG) and methylprednisolone, which significantly improved the symptoms. Serological testing later was positive for antileucine-rich glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some studies suggest ( 9 11 , 23 ) that effective and long-term immunotherapy should be given to prevent long-term complications, including hippocampal atrophy ( 23 ) and sustained memory impairment ( 13 ). Second-line drugs can be added to the therapy of patients ( 23 , 24 ) who did not respond well to the first-line drugs or had a recurrence, including rituximab, MMF, or cyclophosphamide. Once cognitive impairment is confirmed, patients should receive immunotherapy ( 9 11 ) and long-term maintenance therapy to relieve their symptoms ( 23 , 24 ), improve prognosis, and avoid intractable epilepsy and hippocampal atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest ( 9 11 , 23 ) that effective and long-term immunotherapy should be given to prevent long-term complications, including hippocampal atrophy ( 23 ) and sustained memory impairment ( 13 ). Second-line drugs can be added to the therapy of patients ( 23 , 24 ) who did not respond well to the first-line drugs or had a recurrence, including rituximab, MMF, or cyclophosphamide. Once cognitive impairment is confirmed, patients should receive immunotherapy ( 9 11 ) and long-term maintenance therapy to relieve their symptoms ( 23 , 24 ), improve prognosis, and avoid intractable epilepsy and hippocampal atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Second-line drugs can be added to the therapy of patients ( 23 , 24 ) who did not respond well to the first-line drugs or had a recurrence, including rituximab, MMF, or cyclophosphamide. Once cognitive impairment is confirmed, patients should receive immunotherapy ( 9 11 ) and long-term maintenance therapy to relieve their symptoms ( 23 , 24 ), improve prognosis, and avoid intractable epilepsy and hippocampal atrophy. Anti-LGI1 Ab encephalitis may recur or become chronic, as well as legacy cognitive sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with reports of literature, 59% of pediatric patients showed normal brain MRI and for those with abnormal results, the majority showed lesions of temporal lobe and hippocampus, which were also in accordance with adult anti-LGI1 encephalitis. Progressive cerebral atrophy was reported only in one adult case (Yelam et al, 2019). However, Szots et al (2017) found the existence of progressive global brain atrophy in patients with LGI1 limbic encephalitis, especially in temporal limbic structures, frontal lobe and the cerebellum, using a volumetric analysis method of the T1-weighted MRI data, despite early immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since antibody titers are yet not established to accurately monitor the clinical course, some authors suggest a comprehensive approach including seizure control, neuropsychological evaluation, and even MRI metrics, such as brain atrophy or white matter integrity (Yelam et al, 2019;Szots et al, 2017). Nonetheless, the latter seems difficult to implement, mainly due to the current barriers of individual brain atrophy measurements (e.g.…”
Section: Discussionmentioning
confidence: 99%